PELAYANAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DI KANTOR URUSAN AGAMA KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN TAHUN 2020 - Sandra "; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Basically, the marriage card management service of the marriage management information system (SIMKAH) is in order to improve services to the community by using an online-based application. The problem in this study is that there are often network disruptions when inputting data for prospective investors so that they experience delays in inputting data and make KUA operators input data outside of working hours. The purpose of this study is to determine the management of marriage card services using the online SIMKAH application in KUA Pangkalan Lesung District, Pelalawan Regency by referring to the theory of public services according to menpan decree No. 63/2003, namely Transparency, Accountability, Conditional, Participatory, Equal Rights and Balance of Rights and Obligations and also using electronic government theory by Richardus Eko Indrijit, namely support ( Support ), ability (Capacity), and benefits (Value). This research method is qualitative with analytical techniques and research informants, namely the Head of the Ministry of Religion Office, Employee Staff of the Ministry of Religion, Head of the Religious Affairs Office, Staff of the Religious Affairs Office, Lurah Office, and the People of Pangkalan Lesung District. Data were collected by the authors using interview and documentation techniques. These Data Analysis techniques are Data Reduction, Data Presentation and Conclusion Drawing. The results of this study are not optimal because there are still shortcomings such as the lack of supporting infrastructure such as marriage card printing printers, the lack of staffing staff only five people and operators who understand technology only one person and there are factors that become obstacles in online SIMKAH services. Keywords : E-Government, Support, Capabilities, Benefits